Lathyrus turcicus (Fabeae, Fabaceae), a new species from Northwestern Türkiye - Hamzaoğlu Ergi̇n (Phytotaxa, 2023)
Some interesting Lathyrus (Fabaceae) specimens were collected from Büyükorhan District in Bursa Province, N.W. Türkiye. The specimens, at first glance, resembled the Lathyrus pallescens (sect. Platystylis) species as a habit, which grows in N. Balkans, Hungary, Romania, C. & S. Russia, Crimea, Transcaucasica and N.E. Türkiye. However, as a result of detailed examination, it was determined that there were some differences. Based on these differences, the specimens were presented to the scientific world as a new species and were named Lathyrus turcicus. The fact that the stipules are shorter than petiole (not longer than petiole); the calyces are glabrous (not hairy); the calyx teeth subequal (not unequal); the standards and wings are almost equal and 13.2–15.3 mm long (not 20–24 mm); the keels 11–13 mm long (not 16–18 mm) and the legumes 7–9 mm wide (not 3–5 mm) are the most obvious attributes that separate Lathyrus turcicus from L. pallescens, that is a close species. Here, a description of the new species, supporting images, chorology, and general ecological preferences were given.